수치해석을 이용한 어선용 수직축 풍력터빈의 기초연구 - 정광열(Kwang-Leol Jeong); 이영길(Young-Gill Lee); 하윤진(Yoon-Jin Ha); 강봉한(Bong Han Kang); 강대선(Dae-Sun Kang) (大韓造船學會 論文集, 2013)
In this study, the flow characteristics and structural safety of a 500W class vertical-axis wind turbines(VAWT) for a fishing boat are investigated by numerical simulations. Guide vanes to increase the performance of the VAWT are investigated. And the best guide vane in the numerical simulations is applied to the VAWT. Also, modal analyses are performed to find out the natural frequencies of the VAWT, and the resonance safety of the VAWT is evaluated. The structural analysis of the VAWT is carried out by one-way FSI(Fluid Structure Interaction). And the results are used for the evaluation of structural safety according to IEC 61400-1 code. Finally, the possibility of the installation of the VAWT on the wheelhouse of a 9.77ton class fishing boat is checked. The results of the present research could be used as one of the fundamental data to design a VAWT for a fishing boat.